SOLAR EPHEMERIS ACCORDING TO SIMON NEWCOMB - Alamul Yaqin (Fakultas Syari'ah dan Hukum UIN Walisongo, 2020)
The development of Falak cannot be separated from the ephemeris table, one of them i.e Simon Newcomb solar ephemeris. This ephemeris was used in the initial calculation of Abdur Rachim, one of Falak Indonesia's experts. The purpose of this study was to determine the accuracy of the Simon Newcomb ephemeris reckoning algorithm and its strengths and weaknesses. This paper use descriptive analysis as the research methodology. The results of this study are this Ephemeris is quite accurate because because there aremany correction terms and consider aspects of the planet's relative motion to the Earth that can be seen in the formula for perturbation and nutation correction. The advantage of this ephemeris,it has a long period correction which is useful for calculating the Sun ephemeris in years far enough from the epoch used and directly uses UT time in its calculations so there is no need to convert UT to TD. The weakness of this ephemeris is that it cannot be done manually because the formula used is too long and there are many formula corrections.